The social construction of weeds: different reactions to an emergent problem by farmers, officials and researchers - VISSOH, VINASSÉHO PIERRE; MONGBO, R.; GBEHOUNOU, GALBERT; HOUKONNOU, DOMINIQUE; AHAHCHEDE, ADAM; RÖLING, Niels; KUYPER, W. THOM (My University, 2007)
Rapid population increase in southern Benin has changed the prevailing system of shifting cultivation into one of more permanent land use. New herbaceous weeds exacerbated rural poverty through crop failure, higher labour inputs, rising costs of production and reduced availability of suitable land. We investigated how different actors reacted to the emergence of weeds, in terms of the construction of knowledge, labour practices and technology development. Weeds have become an important cause of rural poverty. Farmers have actively engaged in technology development and new labour practices have emerged. Officials early on did report weed problems, especially where export crops were concerned. Researchers have not translated the new weed problem into a research priority until very recently, resulting in limited and inappropriate weed management technologies. The challenge of the research of which this study is part is to optimize weed management, by combining emergent indigenous weed management practices with scientific knowledge.
Keywords: Indigenous technologies; labour shortage; permanent land cultivation; population pressure; rural poverty; stakeholder diversity